Student Program Psychological Negative Impacts of Online Learning in PGSD Study at Indonesian Christian University Toraja - Irene Hendrika Ramopoly; Charlie Baka (Budapest International Research and Critics University, 2022)
The online learning process during the COVID-19 pandemic has various impacts, such as positive and negative impacts on the physical, social, and psychological. The focus of this research is to examine the negative psychological impact of online learning. The negative psychological impacts experienced by students of the PGSD Study Program at the Indonesian Christian University Toraja during the online learning process are decreased learning motivation, anxiety, anxiety, worry, panic, stress, and confusion. This type of research is descriptive quantitative research. The population in this study were odd semester students, namely semester 3, semester 5, and semester 7 who were active students in the Makale class of the PGSD Study Program, Indonesian Christian University Toraja. The sample selection in this study used a purposive sampling technique. The number of research subjects was 135 people, consisting of semester 3 and 7 even semester students of the Indonesian Christian University Toraja PGSD class. The expected results and outcomes of this research are to produce references about the psychological impact of online learning.